3x-2=3(y-2)

Simple and best practice solution for 3x-2=3(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2=3(y-2) equation:


Simplifying
3x + -2 = 3(y + -2)

Reorder the terms:
-2 + 3x = 3(y + -2)

Reorder the terms:
-2 + 3x = 3(-2 + y)
-2 + 3x = (-2 * 3 + y * 3)
-2 + 3x = (-6 + 3y)

Solving
-2 + 3x = -6 + 3y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 3x = -6 + 2 + 3y

Combine like terms: -2 + 2 = 0
0 + 3x = -6 + 2 + 3y
3x = -6 + 2 + 3y

Combine like terms: -6 + 2 = -4
3x = -4 + 3y

Divide each side by '3'.
x = -1.333333333 + y

Simplifying
x = -1.333333333 + y

See similar equations:

| n/3-4.6=21.6 | | 10-2x^2=-98 | | 12:18/7 | | 2(2x+3)=5x-5 | | 3x+2y+3z=2 | | 2.4=108 | | X^5=4+3logx | | z=1.95 | | 12/1:18/7 | | m+3=2m-1 | | 7/8=3/x-6 | | 3x-2+y-2=60 | | -3x=-12+-10 | | 4(6t+4)=4(5t-5) | | 6r-(r+3)=10-(7-5r) | | 7v/8=21 | | X/4-x/12=2 | | 2x-y+z=-11 | | -1+2x=28+13 | | t/6-2=11 | | kx-3=5 | | u/7=17.92 | | P=344x-560 | | 8v=20.40 | | 3n+8+12n-5-7n+11= | | X-11/2=9 | | 7x=2/3 | | 8/1=.22/n | | 1/7(-21x-2) | | 3x+88=14x | | 6q-4=2q-12 | | 56=9w-w |

Equations solver categories